IMPLEMENTASI NILAI KESETARAAN GENDER DALAM KEBIJAKAN DAN KEGIATAN AKADEMIK ORGANISASI DI UIN DATOKARAMA PALU - Esy Kurniati Asiama; Fachriza Ariyadi; Muthia (Musawa: Journal for Gender Studies, 2026)
This study aims to analyze the implementation of gender equality values in institutional policies and the academic activities of student organizations at UIN Datokarama Palu. Employing a qualitative approach with a descriptive design, data were collected through in-depth interviews, participant observation, and document analysis of university regulations, student organizational structures, and ongoing academic programs. The findings indicate that UIN Datokarama Palu has established a foundation for gender-responsive policies through leadership commitment to preventing sexual violence, equitable access to scholarships regardless of gender, and the involvement of women in academic and organizational structures. However, the implementation of gender equality at the student organization level continues to face challenges, including patriarchal dominance in leadership positions, gender-role stereotypes reflected in the distribution of organizational responsibilities, and the limited availability of programs that promote equal participation. The study recommends strengthening gender mainstreaming through formal rector regulations, enhancing the role of a campus gender studies unit, and providing inclusive leadership training for student organizations.